From Abyssinian to Zion : a guide to Manhattan's houses of worship - Dunlap, David W. (Columbia University Press, 2004)
From modest chapels to majestic cathedrals, and historic synagogues to modern mosques and Buddhist temples: this photo-filled, pocket-size guidebook presents 1,079 houses of worship in Manhattan and lays to rest the common perception that skyscrapers, bridges, and parks are the only defining moments in the architectural history of New York City. With his exhaustive research of the city's religious buildings, David W. Dunlap has revealed (and at times unearthed) an urban history that reinforces New York as a truly vibrant center of community and cultural diversity. Published in conj.